INFLUENCE INCOME DIVERSIFICATION, BANK LIQUIDITY, AND FINANCIAL LAVERAGE ON PROFITABILITY WITH BANK EFFICIENCY, AS INTERVENING VARIABLES IN SHARIA COMMERCIAL BANKS 2015-2019 - Novita Sari; Arna Asna Annisa, MSI (Universitas 17 Agustus 1945 Surabaya, 2021)
Abstract The purpose of this study was to determine the effect of Income Deverfication, Bank Liquidity, and Financial Laverage on Profitability with Bank Efficiency, as an Intervening variable in Islamic Commercial Banks in 2015-2019. This research uses quantitative research by using regression analysis as data analysis. This study uses secondary data in the form of time series annual data of Islamic commercial banks for the period 2015 to 2019. The required data is then analyzed using the SPSS 22 application tool. The results show that FBI, FDR have a positive and non-significant effect on ROA, DER has a negative and no effect. significant effect on ROA, FBI, FDR positive and not significant effect on ROA, DER negatively and not significant on ROA, BOPO positive and significant effect on ROA.Keywords: Income Deverfication, Bank Liquidity, and Financial Laverage on Profitability with Bank EfficiencyAbstrak Tujuan penelitian ini dilakukan adalah untuk mengetahui pengaruh Pengaruh Income Deverfication, Bank Liquidity, dan Financial Laverage terhadap Profitability dengan Bank Effeciency, sebagai variabel Intervening pada Bank Umum Syariah Tahun 2015-2019. Penelitian ini menggunakan jenis penelitian kuantitatif dengan menggunakan analisis regresi sebagai analisi data. Penelitian ini menggunakan data sekunder berbentuk time series data tahunan bank umum syariah periode 2015 sampai 2019. Data yang diperlukan kemudian dianalisis menggunakan alat bantu aplikasi SPSS 22. Hasil penelitian menunjukan bahwa FBI, FDR berpengaruh positif dan tidak singnifikan terhadap ROA, DER berpengaruh negatif dan tidak singnifikan terhadap ROA, FBI, FDR berpengaruh positif dan tidak singnifikan terhadap BOPO, DER berpengaruh negatif dan tidak singnifikan terhadap BOPO, BOPO berpengaruh positif dan singnifikan terhadap ROA.Kata Kunci: Income Deverfication, Bank Liquidity, dan Financial Laverage terhadap Profitability dengan Bank Effeciency.